Naphthyl derivative for regulating and controlling photoresponse through thermal phase change as well as preparation method and application of naphthyl derivative
By introducing halogen atoms in the rings and using thermal phase regulating optical response, the problem of insufficient research on organic molecular crystals in existing technologies has been solved, and the transformation of light -sensitivity is realized. New materials for light switch.
Patent Information
- Application Number
- CN202411497502.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-25
AI Technical Summary
In the prior art, there are few researches on organic molecular crystals, and it is difficult to design organic molecular crystals with novel structures and excellent properties.
By introducing halogen atoms in the rings, using hydrogen bonds or halogen bond interactions to regulate the accumulation method of molecular crystals, and regulate the light response through thermal phase change to obtain a pyrine -based derivatives that can show light sensitivity characteristics under the light Essence
The transformation of light -to -light sensitivity is realized, providing new materials for optical drivers and optical switching, and provided new ideas for designing optical response molecular crystals.
Smart Images

Figure CN119371335A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a molecular crystal, and in particular to a naphthyl derivative capable of regulating light response through thermal phase change, and a preparation method and application thereof. Background Art
[0002] Photons can penetrate various media in a non-contact manner to transmit energy and information. Photomechanically responsive materials are good examples of converting light energy into mechanical energy and can be applied to optical switches, soft robots, micropumps, and micromachines. After photoreactive molecules are prepared into crystals, they often exhibit macroscopic photomechanical properties such as twisting, curling, jumping, bending, and expansion under light conditions. They have important application value in the fields of optical switches, photoactuators, artificial muscles, etc.
[0003] Currently, the reports are mainly focused on complexes and polymers, and there are still few studies on organic molecular crystals. Therefore, it is still challenging to design organic molecular crystals with novel structures and excellent performance. According to the survey, in order to obtain organic molecular crystals with excellent performance, it is necessary to have functional groups that can undergo photochemical reactions and groups that are conducive to effective stacking in the molecular structure. Based on the characteristics of the naphthalene ring such as good planarity, multiple reaction sites and easy modification, the applicant adjusts the stacking mode of the crystal by changing the substituents and changing their positions, and further introduces halogen atoms into the aromatic ring to control the arrangement mode by using hydrogen bonds or halogen bonds. It is expected to obtain molecular crystals that satisfy the Schmidt topological rules and undergo [2+2] cycloaddition reactions. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a naphthyl derivative that regulates light response through thermal phase change, and a preparation method and application thereof. The naphthyl derivative described in the present invention can obtain a photo-inert crystal form through a solvent method, and the photo-inert crystal form can be converted into another crystal form that exhibits photosensitivity under specific heating conditions. The photosensitive crystal form after thermal conversion can be used in the fields of photo-driven driving and optical switching.
[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0006] A naphthyl derivative, the molecular formula of which is C 23 H 19 Cl1N2, chemical name is (2Z, 4E)-2-(3-chlorophenyl)-5-(7-(dimethylamino)naphthalen-2-yl)penta-2,4-dibenzonitrile, structure is shown in the following formula (I):
[0007]
[0008] The naphthyl derivative of the present invention is in the form of yellow powder and is a molecular aggregate state. The applicant has found in experiments that a photo-inert crystal form can be obtained by a solvent method, and the photo-inert crystal form is referred to as the Y crystal form in this application. After heating phase change, another photosensitive crystal form is obtained, and the photosensitive crystal form is referred to as the Y transition crystal form in this application.
[0009] The second aspect of the present invention provides a method for preparing the above naphthyl derivatives, comprising: placing (E)-3-(7-(dimethylamino)naphthalen-2-yl)acrolein and 2-(3-chlorophenyl)acetonitrile in an alcohol solvent, reacting in the presence of an alkali catalyst, filtering after the reaction is completed, collecting the filter cake, and drying to obtain the product.
[0010] The naphthyl derivative of the present invention is synthesized by Knoevenagel condensation reaction from (E)-3-(7-(dimethylamino)naphth-2-yl)propenal and 2-(3-chlorophenyl)acetonitrile. In the preparation method of the naphthyl derivative, the ratio of (E)-3-(7-(dimethylamino)naphth-2-yl)propenal and 2-(3-chlorophenyl)acetonitrile is a stoichiometric ratio; the alcohol solvent is preferably methanol or ethanol, or a combination of the two; the amount of the alcohol solvent is preferably such that it can dissolve all the raw materials participating in the reaction, and preferably, the amount is calculated according to the standard of adding 2 to 10 mL of the alcohol solvent to 1 mg of (E)-3-(7-(dimethylamino)naphth-2-yl)propenal. The alkaline catalyst is a conventional alkaline catalyst selected in the Knoevenagel condensation reaction, such as one or a combination of two or more selected from sodium hydroxide, sodium carbonate, neutral alumina, basic alumina and triethylamine; the amount of the alkaline catalyst is preferably 0.2 to 0.4 times the mass of (E)-3-(7-(dimethylamino)naphthalene-2-yl)acrolein.
[0011] In the above-mentioned method for preparing naphthyl derivatives, the reaction can be carried out under heating or without heating, preferably without heating, usually at 20-30° C. When the reaction is carried out at 20-30° C., the reaction time is preferably controlled within 3-6 hours.
[0012] The raw material (E)-3-(7-(dimethylamino)naphthalen-2-yl)acrolein involved in the preparation method of the naphthyl derivatives has a structure as shown in the following formula (II), and can be prepared with reference to the invention patent application with publication number CN117720436A, or can be synthesized by a self-designed route;
[0013]
[0014] In the present application, (E)-3-(7-(dimethylamino)naphthalen-2-yl)acrolein is preferably prepared by the following method:
[0015] 1) 7-bromonaphthalene-2-ol and dimethylamine are used as raw materials and water is used as solvent. Solvothermal reaction is carried out in the presence of sodium pyrosulfite. After the reaction is completed, ethyl acetate and water are used for separation. The organic layer is taken and spin-dried to obtain a crude intermediate product.
[0016] In this step, the amount of sodium metabisulfite added is usually 1 to 2 times the mass of 7-bromonaphthalene-2-ol; the solvent thermal reaction is preferably carried out at 130 to 150° C., and the reaction time is controlled to be 96 to 120 hours.
[0017] Preferably, the crude product is purified before use in subsequent steps. Specifically, the crude product can be purified by silica gel column chromatography (n-hexane / ethyl acetate = 20-50:1, volume ratio) to obtain the purified intermediate product 7-bromo-N,N-dimethylnaphthalene-2-amine.
[0018] 2) The intermediate product, 3,3-diethoxyprop-1-ene, an organic solvent, a palladium catalyst and a weak base are placed in a reaction vessel, tetrabutylammonium acetate is added or not, and a heck reaction is carried out under an atmosphere protection condition. After the reaction is completed, the reaction is acidified and alkalized to obtain a crude product of (E)-3-(7-(dimethylamino)naphthalen-2-yl)acrolein.
[0019] In this step, the organic solvent can be tetrahydrofuran, N,N-dimethylformamide or 1,4-dioxane; the weak base can be one or a combination of triethylamine, diethylamine, sodium carbonate, potassium carbonate or cesium carbonate, and its dosage is usually 1 to 3 times the mass of the intermediate product. The amount of tetrabutylammonium acetate added is usually 0.5 to 1.0 times the mass of the intermediate product. For palladium catalyst, its selection and dosage are conventional choices in the prior art, preferably tetrakis(triphenylphosphine)palladium and / or bistriphenylphosphine palladium dichloride, and its dosage is preferably 0.1 to 0.3 times the weight of the intermediate product. When the heck reaction is usually carried out at 110 to 130°C, the reaction time is usually controlled at 96 to 120 hours.
[0020] Preferably, the obtained crude product is purified before being used in the subsequent steps. Specifically, the obtained crude product can be further purified by silica gel column chromatography (n-hexane / ethyl acetate = 20-50:1, volume ratio) to obtain purified (E)-3-(7-(dimethylamino)naphthalen-2-yl)acrolein.
[0021] The third aspect of the present invention provides two crystal forms of the naphthyl derivative, one of which is a Y crystal form, which belongs to the orthorhombic system, the Pna21 space group, and the unit cell parameters are: α=90.00°,β=90.00°,γ=90.00°. The crystal form is yellow needle-shaped crystals and is optically inert.
[0022] Another crystal form of the naphthyl derivative provided by the present invention is a Y-transformation crystal form, which belongs to a cubic crystal system, a P-1 space group, and a unit cell parameter: α=76.307(3)°,β=84.908(3)°,γ=82.954(3)°. The crystal form is orange needle-shaped crystals and exhibits photosensitivity.
[0023] The fourth aspect of the present invention provides a method for preparing the two crystal forms of the naphthyl derivatives, wherein:
[0024] The preparation method of crystal form Y is: the naphthyl derivative is placed in a mixed solvent consisting of dichloromethane and ethanol or methanol for recrystallization, wherein the volume ratio of dichloromethane to ethanol or methanol is 1:3-10, and more preferably 1:6-7.
[0025] The preparation method of the Y-transformation crystal form is as follows: heating the Y-transformation crystal form to a phase transition point, and maintaining the temperature at the temperature until the color of the crystal changes completely to orange. The phase transition point is 150-153°C. Under normal circumstances, the color of the crystal changes completely from yellow to orange when the temperature is maintained for 10-30 minutes, preferably for 20-30 minutes.
[0026] The preparation method of the Y-transformation crystal form can also be obtained by solvent crystallization, specifically, the naphthyl derivative is placed in a mixed solvent consisting of dichloromethane and n-hexane or petroleum ether for recrystallization. The volume ratio of dichloromethane to n-hexane or petroleum ether is preferably 1:3-10, and more preferably 1:6-7.
[0027] The applicant has found through experiments that the Y-transformed crystal form exhibits photosensitivity, and its light response range extends from ultraviolet light to green light in visible light, which is specifically manifested as backlight bending, and the light response is reversible. The crystal form that bends after the light response can be restored to its original state when away from ultraviolet light or heated. The Y crystal form exhibits photoinertness, and has no photoresponse phenomenon under ultraviolet and visible light irradiation, but a unique SCSC phase transition occurs when heated to near the melting point. This thermal phase change changes the stacking of the Y crystal form and transforms it into a Y-transformed crystal form that can respond to light, realizing the transformation from photoinertness to photosensitivity. This tandem reaction connecting thermal phase change and photoresponse is rarely found in molecular crystal forms and is worth in-depth research. Similarly, this means of regulating photoresponse through thermal phase change also provides new ideas for designing and preparing photoresponsive molecular crystal forms.
[0028] The fifth aspect of the present invention provides a composite film, comprising the above-mentioned Y-transformation crystal form. The thickness of the composite film is determined according to needs and can be 25-150 μm.
[0029] The above composite film can be prepared by conventional methods, preferably as follows: grind the above Y transformation crystal form and disperse it in a solvent, add the substrate, stir evenly, pour the obtained viscous liquid into a mold, dry, and peel off. The solvent can be ethanol or water; the substrate can be one selected from PVA (polyvinyl alcohol), chitosan, polyvinylidene fluoride and polypropylene, preferably a 10-25wt% PVA aqueous solution, more preferably a 10wt% PVA aqueous solution; the mass ratio of the Y transformation crystal form to the PVA aqueous solution can be 1-3:10.
[0030] A sixth aspect of the present invention provides a photoactuator made from the above-mentioned composite film.
[0031] Specifically, the composite film can be made into the photoactuator by cutting, folding, and multiple fixed connections, and the shape of the composite film is two-dimensional or three-dimensional.
[0032] The seventh aspect of the present invention provides the use of the above-mentioned Y-transformation crystal form or the above-mentioned composite film in photo-driven driving.
[0033] Furthermore, irradiation is performed using 365 nm ultraviolet light extending to green light (such as 490 nm) in the visible light.
[0034] The seventh aspect of the present invention provides the use of the above-mentioned Y-transformation crystal form or the above-mentioned composite film in the preparation of a light-operated switch.
[0035] After coating the surface of the composite film with conductive silver paste, the composite film becomes conductive. After connecting it to a patch circuit, it can be made into a light-controlled switch, which is expected to be used in fields such as molecular robots.
[0036] Compared with the prior art, the present invention is characterized in that:
[0037] 1. The naphthyl derivative provided by the present invention is a molecular aggregation state, and a Y crystal form can be obtained by crystallization in a solvent, and the Y crystal form exhibits photoinertness. When the Y crystal form is heated to near the melting point, a unique SCSC phase transition will occur. The thermal phase transition changes the stacking of the Y crystal form to transform it into a Y transition crystal form that can respond to light, thereby realizing the transformation from photoinertness to photosensitivity. The tandem reaction connecting the thermal phase transition and the photoresponse in the present invention is rarely found in molecular crystals, and is worthy of in-depth research. Moreover, the present invention provides a new idea for the design and preparation of photoresponsive molecular crystals by means of regulating the photoresponse through thermal phase transition.
[0038] 2. A composite film is made by combining the photoresponsive Y-transition crystal with PVA. The resulting composite film inherits the photoresponsive characteristics of the Y-transition crystal while also enhancing the mechanical properties of the molecular crystal. The composite film can be bent and twisted without affecting its photoresponsive performance, and is expected to be used in optical brakes.
[0039] 3. Conductive silver paste is coated on the surface of the composite film to make it conductive, and then it can be connected to a patch circuit to make a light-controlled switch, which is expected to be used in molecular robotics and other fields.
[0040] 4. The preparation method involved in the present invention has mild reaction conditions, the reagents used are relatively common and less polluting, safe and reliable; the intermediate products involved do not require harsh reaction conditions and storage conditions, and the synthesis is simple, suitable for a wide range of applications. Among them, the Y transformation crystal form is chemically stable and can be stored for a long time in a light-proof state, while the Y crystal form does not need to be stored in a light-proof state and has stable chemical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is the hydrogen nuclear magnetic resonance spectrum of the intermediate product 7-bromo-N,N-dimethylnaphthalene-2-amine prepared in Example 1.
[0042] Figure 2 This is the hydrogen nuclear magnetic resonance spectrum of (E)-3-(7-(dimethylamino)naphthalen-2-yl)acrolein prepared in Example 1.
[0043] Figure 3 These are the hydrogen nuclear magnetic resonance spectrum and carbon nuclear magnetic resonance spectrum of the naphthyl derivative (2Z,4E)-2-(3-chlorophenyl)-5-(7-(dimethylamino)naphthalen-2-yl)penta-2,4-dibenzonitrile prepared in Example 1, wherein (a) is the hydrogen spectrum and (b) is the carbon spectrum.
[0044] Figure 4 This is the powder X-ray diffraction spectrum of the Y-transformation crystal prepared in Example 5.
[0045] Figure 5 This is the powder X-ray diffraction spectrum of the Y crystal form prepared in Example 4.
[0046] Figure 6 This is the molecular stacking diagram of the Y-transformation crystal prepared in Example 5.
[0047] Figure 7 This is the molecular stacking diagram of the Y crystal form prepared in Example 4.
[0048] Figure 8 This is the thermogravimetric analysis diagram of the Y-transformation crystal prepared in Example 5.
[0049] Fig. 9 This is the thermogravimetric analysis diagram of the Y crystal form prepared in Example 4.
[0050] Fig.10These are light response diagrams of the Y-transformation crystal prepared in Example 5; wherein, (a) is a light response diagram of the Y-transformation crystal when the Y-transformation crystal is irradiated with visible light, (b) is a light response diagram of the Y-transformation crystal when the Y-transformation crystal is irradiated with 365nm ultraviolet light, (c) is a light response diagram of the Y-transformation crystal when the Y-transformation crystal is irradiated with 405nm ultraviolet light, and (d) is a light response diagram of the Y-transformation crystal when the Y-transformation crystal is irradiated with 490nm green light.
[0051] Fig.11 These are diagrams of the light response of the composite film in Application Example 2; wherein, (a) is a diagram of the initial state of the composite film, (b) is a diagram of the light response of the composite film under illumination of a wavelength of 490 nm from bottom to top, and (c) is a diagram of the light response of the composite film under illumination of a wavelength of 295 nm from bottom to top.
[0052] Fig.12 The diagrams are of the light response of the composite film after being coated with conductive silver paste and connected to the patch circuit in Application Example 3; wherein, (d) is a simulated design diagram of the light-controlled circuit, (e) is a real picture of the circuit in an open circuit state, and (f) is a real picture of the composite film being bent under 490nm light and connecting the circuit to light up the small lamp. DETAILED DESCRIPTION
[0053] In order to better explain the technical solution of the present invention, the present invention is further described in detail below in conjunction with embodiments, but the embodiments of the present invention are not limited thereto.
[0054] Example 1: Preparation of naphthyl derivatives
[0055] 1) Take 2g of 7-bromonaphthalene-2-ol, 3.2g of sodium pyrosulfite, 8g of water, and 5.04g of dimethylamine, place them in a hydrothermal reactor and react in an oven at 140°C for 96h. After the reaction is completed, separate them with ethyl acetate and water, take the organic layer and spin dry it, and separate the residue on a silica gel column (n-hexane / ethyl acetate = 30:1, volume ratio) to obtain the intermediate product 7-bromo-N, N-dimethylnaphthalene-2-amine. The nuclear magnetic resonance hydrogen spectrum of the intermediate product is as follows Figure 1 shown.
[0056] 2) Take 3g of 7-bromo-N,N-dimethylnaphthalene-2-amine, 4.5g of 3,3-diethoxyprop-1-ene, 0.45g of bistriphenylphosphine palladium dichloride, and 6g of potassium carbonate and dissolve them in 30mL of N,N-dimethylformamide. Stir and react in a constant temperature oil bath at 120°C for 96h under the protection of nitrogen atmosphere. After the reaction, add 1mL of hydrochloric acid for 1h (deprotection to expose the aldehyde group), and then alkalize with sodium bicarbonate (to remove excess acid). After alkalization, separate with dichloromethane and water, take the organic layer and spin dry, and separate the residue on a silica gel column (n-hexane / ethyl acetate = 30:1, volume ratio) to obtain (E)-3-(7-(dimethylamino)naphthalene-2-yl)acrolein. The nuclear magnetic resonance hydrogen spectrum of the obtained (E)-3-(7-(dimethylamino)naphthalene-2-yl)acrolein is as follows: Figure 2 shown.
[0057] 3) 30 mg of (E)-3-(7-(dimethylamino)naphthalen-2-yl)acrolein, 20 mg of 2-(3-chlorophenyl)acetonitrile, and 8 mg of sodium hydroxide were dissolved in 35 mL of ethanol and stirred at 25° C. for 4 h. After the reaction was completed, the mixture was filtered, the filter cake was collected, and dried to obtain a yellow powder weighing 35 mg with a yield of 73.24%.
[0058] The yellow powder obtained in this example was subjected to H NMR and C NMR analysis. Figure 3 Therefore, it can be determined that the obtained yellow powder is the naphthyl derivative of the present invention, namely (2Z, 4E)-2-(3-chlorophenyl)-5-(7-(dimethylamino)naphthalen-2-yl)penta-2,4-dibenzonitrile, whose structure is shown in the following formula (I):
[0059]
[0060] Example 2: Preparation of naphthyl derivatives
[0061] Example 1 was repeated, except that in step 3), basic alumina was used instead of sodium hydroxide, and methanol was used instead of ethanol.
[0062] Finally, 28 mg of yellow powder was obtained with a yield of 58.6%.
[0063] The yellow powder obtained in this example was subjected to H NMR and C NMR analyses, confirming that the yellow powder obtained was the naphthyl derivative of the present invention.
[0064] Example 3: Preparation of naphthyl derivatives
[0065] Example 1 was repeated, except that in step 3), triethylamine was used instead of sodium hydroxide.
[0066] Finally, 25 mg of yellow powder was obtained with a yield of 52.3%.
[0067] The yellow powder obtained in this example was subjected to H NMR and C NMR analyses, confirming that the yellow powder obtained was the naphthyl derivative of the present invention.
[0068] Example 4: Preparation of Crystal Form Y
[0069] 10 mg of the naphthyl derivative prepared by the method described in Example 1 was placed in a 10 mL glass bottle, 1 mL of dichloromethane was added, and 6 mL of ethanol was added after dissolution. The mixture was allowed to stand for 120 h and yellow needle-like crystals were observed to precipitate in the glass bottle. The crystals were collected and dried and recorded as crystal form Y. The yield was 98%.
[0070] Example 5: Preparation of Y-transformation crystal
[0071] Take 10 mg of the Y-type crystal prepared by the method described in Example 4, heat it to 150°C, and maintain it at this temperature for 20 minutes. The crystal changes from the initial yellow to orange. Stop heating, cool to room temperature, collect the crystals, dry them, and record them as Y-transformation crystal. The yield is 95%.
[0072] The two crystals obtained in Example 4 and Example 5 were characterized:
[0073] 1. Powder X-ray Diffraction Analysis
[0074] The obtained Y transformation crystal form and Y crystal form were subjected to powder XRD analysis, and the results were as follows: Figure 4 and Figure 5 As shown, it can be seen that the two crystals have completely different stacking patterns.
[0075] 2. Single crystal X-ray diffraction analysis
[0076] The Y-transform and Y-form with appropriate sizes were selected and placed on a SuperNova X-ray single crystal diffractometer using graphite monochromatized Mo-Kα radiation. The main crystal data and correction parameters of the two crystal forms are shown in Table 1 below, their partial bond length and bond angle data are shown in Table 2 and Table 3 below, and the molecular stacking diagrams of the two crystal forms are shown in Table 3 and Table 4 respectively. Figure 6 and Figure 7 shown.
[0077] Table 1: Crystal data and structural optimization parameters of Y transformation crystal form / Y crystal form
[0078]
[0079] Table 2: Some bond lengths of Y-transform and bond angle / ° data
[0080]
[0081]
[0082]
[0083] Table 3: Some bond lengths of Y crystal form and bond angle / ° data
[0084]
[0085] 3. Thermogravimetric analysis
[0086] Thermogravimetric analysis was performed on the Y transformation crystal form and the Y crystal form, and the results were as follows: Figure 8 and Fig. 9 As shown, no phase change occurs in the Y transformation crystal form before melting, and the Y crystal form undergoes a thermal phase change at the melting point.
[0087] 4. Light Response Behavior Analysis
[0088] The specific response of the Y-transformation crystal under different wavelengths of light is as follows: Fig.10 As shown, it can be seen that the Y-transformed crystal produces obvious backlight bending after being exposed to light.
[0089] Example 6: Preparation of Crystal Form Y
[0090] 10 mg of the naphthyl derivative prepared by the method described in Example 1 was placed in a 10 mL glass bottle, 1 mL of dichloromethane was added, and 6 mL of methanol was added after dissolution. The mixture was allowed to stand for 132 hours for evaporation. Yellow needle-shaped crystals were observed to precipitate in the glass bottle. The crystals were collected and dried. The yield was 97%. The yellow needle-shaped crystals were analyzed by single crystal diffraction and the like, and it was determined that the yellow needle-shaped crystals were the Y crystal form described in the present invention.
[0091] Example 7: Preparation of Crystal Form Y
[0092] The preparation was carried out according to the method of Example 4, except that the amount of ethanol was changed to 3 mL. After standing and volatilizing for 96 hours, yellow needle-shaped crystals were precipitated in the glass bottle, and the crystals were collected and dried, with a yield of 96%. The obtained yellow needle-shaped crystals were subjected to single crystal diffraction and other analyses, and it was determined that the obtained yellow needle-shaped crystals were the Y crystal form described in the present invention.
[0093] Example 8: Preparation of Y-transformation crystal
[0094] 10 mg of the naphthyl derivative prepared by the method described in Example 1 was placed in a 10 mL glass bottle, 1 mL of dichloromethane was added, and 6 mL of petroleum ether was added after dissolution, and the mixture was allowed to stand for 60 hours to evaporate. Orange needle-shaped crystals were observed to precipitate in the glass bottle, and the crystals were collected and dried. The yield was 98%. The obtained orange needle-shaped crystals were analyzed by single crystal diffraction and the like, and it was determined that the obtained orange needle-shaped crystals were the Y transformation crystal form described in the present invention.
[0095] Example 9: Preparation of Y-transformation crystal
[0096] 10 mg of the Y crystal form prepared by the method described in Example 6 was taken and heated to 153°C and maintained at this temperature for 25 minutes. The crystals completely changed from the initial yellow to orange. The heating was stopped, cooled to room temperature, and the crystals were collected and dried. The yield was 95%. The obtained orange needle-shaped crystals were analyzed by single crystal diffraction and the like, and it was determined that the obtained orange needle-shaped crystals were the Y transformation crystal form described in the present invention.
[0097] Application Example 1: Preparation of composite membrane
[0098] The Y-transformation crystal prepared by the method described in Example 5 was placed in an agate mortar and ground into powder, and then the powder was mixed with a 10wt% PVA aqueous solution at a mass ratio of 1g:2mL and stirred to obtain a uniform viscous liquid, which was dripped into a glass mold with a dry and clean surface and dried in a constant temperature oven at 30°C. After the solvent was completely volatilized, it was peeled off from the glass mold to obtain a composite film.
[0099] Application Example 2: Photoresponse Analysis of Composite Films
[0100] The composite film prepared in Application Example 1 was cut into rectangular pieces of 1 cm × 0.5 cm, and one end of the piece was fixed to one end of a glass sheet, and a weight twice the weight of the composite film was fixed to the other end. The composite film was irradiated from bottom to top with 490 nm green light or 295 nm ultraviolet light, and the process was recorded with a camera, as shown in FIG. Fig.11 It was found that under 490nm green light or 295nm ultraviolet light, the composite film quickly bends backlight and can easily lift objects twice its own weight, indicating that the composite film is expected to be used in optical brakes.
[0101] Application Example 3: Analysis of the Light Response of a Photosensitive Switch
[0102] The composite film prepared in Application Example 1 was cut into rectangular pieces of 2 cm×0.5 cm, and a conductive silver paste (brand: Yingxun, model: EN-06B8) was coated on one side. The composite film coated with the conductive silver paste was placed in a 30°C oven for drying for 24 hours and then taken out. The dried composite film was adhered to the patch circuit with the conductive silver paste, and the patch circuit adhered with the composite film was placed in a 30°C oven for drying for 24 hours. The composite film was irradiated from bottom to top with green light of 490 nm wavelength, and the process was recorded with a camera, as shown in FIG. Fig.12 It was found that under the irradiation of green light with a wavelength of 490nm, the composite film bent upward and contacted the switch contact, successfully lighting up the small lamp.
Claims
1. A naphthyl derivative that regulates light response through thermal phase transition, the molecular formula of which is C 23 H 19 Cl1N2, chemical name is (2Z, 4E)-2-(3-chlorophenyl)-5-(7-(dimethylamino)naphthalen-2-yl)penta-2,4-dibenzonitrile, structure is shown in the following formula (I):
2. The method for preparing the naphthyl derivative according to claim 1, characterized in that: (E)-3-(7-(dimethylamino)naphthalen-2-yl)acrolein and 2-(3-chlorophenyl)acetonitrile are placed in an alcohol solvent and reacted in the presence of an alkali catalyst. After the reaction is completed, the filter is filtered, the filter cake is collected, and dried to obtain the product.
3. The preparation method according to claim 2, characterized in that: The alcohol solvent is methanol and / or ethanol; the alkali catalyst is one or a combination of two or more of sodium hydroxide, sodium carbonate, aluminum oxide, triethylamine and diethylamine.
4. A crystal form of the naphthyl derivative according to claim 1, which is a Y crystal form, which belongs to the orthorhombic system, the Pna21 space group, and the unit cell parameters are: α=90.00°, β=90.00°, γ=90.00°.
5. The method for preparing the crystal form according to claim 4, characterized in that: The naphthyl derivative according to claim 1 is placed in a mixed solvent consisting of dichloromethane and ethanol or methanol and recrystallized to obtain the product.
6. A crystal form of the naphthyl derivative according to claim 1, which is a Y-transformation crystal form, which belongs to the cubic system, the P-1 space group, and the unit cell parameters are: α=76.307(3)°, β=84.908(3)°, γ=82.954(3)°.
7. The method for preparing the crystal form according to claim 6, characterized in that: The Y crystal form according to claim 4 is heated to a phase transition point, and kept at this temperature until the color of the crystals completely turns orange; or The naphthyl derivative according to claim 1 is placed in a mixed solvent consisting of dichloromethane and n-hexane or petroleum ether and recrystallized to obtain the product.
8. A composite film, characterized in that: Including the crystal form described in claim 6.
9. A photoactuator, characterized in that: Made from the composite membrane described in claim 8.
10. Use of the crystal form according to claim 6 or the composite film according to claim 8 in photo-driven driving or in the preparation of a light-controlled switch.
Citation Information
Patent Citations
Organic crystal with thermal phase change induced mechanical behavior and fluorescence enhancement as well as preparation method and application of organic crystal
CN117720436A
Diphenyl acrylonitrile flexible crystal material as well as preparation method and application thereof
CN117800874A
Photopolymerizable composition
JP1986270747A
Cited By
Molecular crystal for realizing broadband light-induced mechanical motion through thermotropic polymorphic transformation as well as preparation and application of molecular crystal
CN121471109A